Personalized computational hemodynamics : models, methods, and applications for vascular surgery and antitumor therapy /: models, methods, and applications for vascular surgery and antitumor therapy. (2020) - Vassilevski, Yuri; Olʹshanskiĭ, Maksim Aleksandrovich, 1971-; Simakov, Sergey; Kolobov, Andrey; Danilov, Alexander
No abstract available